Cull Whole Peanuts as a Feed Supplement for Beef Cows - Bob Myer; Gary Hill (EDIS)
AN212, a 3-page illustrated fact sheet by Bob Myer and Gary Hill, presents the results of a two-year study conducted at NFREC in Marianna, Florida to evaluate raw whole cull peanuts as a potential protein and energy supplement feed for beef cows. Published by the UF Department of Animal Science, January 2009.